Perancangan Sistem Informasi Pemesanan Jasa Penyelenggara Pernikahan Berbasis Web pada CV. Sahabat Decoration - Rifka Heryadi; Bagas Setiyaki Wicaksono (CV. Multi Kreasi Media, 2022)
Developments in technology and information are growing rapidly. With these developments, it seems very clearly affect the speed and accuracy in the delivery of information. There are still a lot of business activities, especially in the process of ordering services which are not in line with current technological developments. That's how the author made a final project regarding the design of a web-based wedding service ordering information system on CV. Friends of decoration, currently managing orders is still manual. Most of all systems that run on orders are still done manually, starting from bookkeeping, marketing, and making financial reports. That way it is possible that during the business process there will be errors in it. The design of the information system in ordering this service is the best solution to overcome the problems that occur in the business. For the development method, the author uses the waterfall model. In making this ordering information system using the PHP programming language and using the MySQL database. This service ordering information system provides information from several common processes that often occur in the process. The results that the authors expect from making this information system can provide fast and precise information.